Design of Ecological Land Remediation Planning and Remediation Mode Based on Spatial Clustering Algorithm - Yao, Yuzhuo (Informatica, 2023)
In order to better realize the design of ecological land consolidation planning and regulation mode, the author proposes a method based on a spatial clustering algorithm. Based on GIS methods such as spatial clustering algorithm and least resistance model, select typical projects and put forward ecological land consolidation planning scheme. Guided by unified engineering construction forms and rigid engineering construction standards, and aiming at regularization and rigidization, traditional land consolidation by means of high-intensity engineering construction, although in the process of stabilizing the amount of cultivated land and improving agricultural production conditions, played a positive role, however, under the current requirements of ecological civilization construction, there is an urgent need for transformation. Through the improvement of ecological land, the ecological improvement is realized, and the need for landscape improvement is more urgent. The study is guided by the theory of landscape ecology, according to the general idea of "landscape pattern evaluation-land remediation function zoning-corridor pattern optimization-patch matrix optimization". The experimental results show: Use Fragstates software to calculate various indicators, the results show that, before and after renovation, the landscape types with the largest landscape ecological security index LESi were all cultivated land, and the smallest one was forest land. Except for the river landscape ecological security index, which dropped by 9.84%, the ecological security of other types of landscapes improved, among them, the largest increase was road (121.29%), followed by forest land (43.10%). According to formulas (1) and (2), the landscape safety index LES of the project area is 0.45 before the renovation, and 0.61 after the renovation, an increase of 35.56%, it shows that through the ecological land consolidation project area, the overall landscape ecological security status has been improved, however, the optimization of river landscape should be strengthened. It is proved that the spatial clustering algorithm can better realize the design of ecological land remediation planning and remediation mode.